2018
DOI: 10.14689/ejer.2018.73.1
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students' Satisfaction Levels on the Quality of Faculty Life

Abstract: School life quality influences students in many ways with factors related to it. For this reason, the quality of life of the school needs to be taken seriously. Satisfaction with school life can contribute to students' positive attitudes toward the school. When the relevant literature is examined, it is observed that a limited number of researches have been conducted in our country. Based on this reason, it has been decided to carry out this research. Research Methods: The screening model was used in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…is mostly discussed in terms of academic success, and the personality, spiritual, emotional and social skills that learners gain are not considered [7,8]. In the literature, many studies examining the effects of quality of school life can be found in the studies conducted on the subject [1,[9][10][11]. When these studies are examined briefly; we can see [12][13][14][15], examining the quality of school life according to some variables (bullying, empathy development, etc.)…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…is mostly discussed in terms of academic success, and the personality, spiritual, emotional and social skills that learners gain are not considered [7,8]. In the literature, many studies examining the effects of quality of school life can be found in the studies conducted on the subject [1,[9][10][11]. When these studies are examined briefly; we can see [12][13][14][15], examining the quality of school life according to some variables (bullying, empathy development, etc.)…”
Section: Issn: 2252-8822 mentioning
confidence: 99%